"Thinking about your pronunciation": Examining phonological self-awareness with a novel task - Kivistö de Souza Hanna; Lintunen Pekka (France, 2025)
Noticing the gap in one's pronunciation is notoriously demanding (Piske, 2008), and yet becoming aware of pronunciation challenges is beneficial for overall pronunciation competence (Kivistö de Souza, 2017). Previous studies on phonological self-awareness have employed global tasks such as journaling (e.g., Kennedy & Blanchet, 2014), and have pointed out that more explicit learning conditions lead to more noticing (White & Ranta, 2002). The objective of this paper is to present an instrument that examines second language phonological awareness by bringing the phonetic detail explicitly into the learners' attention. The participants were 33 L1 Finnish advanced university learners of English attending an undergraduate course on English phonetics and phonology. At the beginning of the semester, the participants provided a speech sample targeting tricky English sounds. At the end of the semester, a "Thinking about your pronunciation" task was administered in which the samples were played back to the participants. They were asked to indicate any pronunciation deviations they could perceive and to elaborate on how they perceived their own intelligibility and their abilities in recognising phonetic and phonological phenomena in their own and others' speech. Our observations with the task indicate that the instrument can be a helpful and reliable tool in tapping into phonological self-awareness.
Proceedings of the 7th International Conference on English Pronunciation: Issues and Practices